Customer service excellence : - Weingand, Darlene E. (American Library Association, 1997)
Future-Driven Library Marketing offers a unique #38; practical program to position #38; market the library as the choice information provider to all of its customers. Darlene Weingand suggests that the best strategies to market the library are future-driven-ones that position the library #38; its products #38; services for success, no matter what the future holds. Regardless of the size #38; type of your library, you will want to use this valuable tool in planning your marketing strategy-now #38; in the future.